The Aesthetical Writings of Giacinto Scelsi - Sciannameo, Franco; Pellegrini, Alessandra Carlotta (Rowman & Littlefield Publishers, 2023)
Giacinto Scelsi (1905-1988), an extraordinary, innovative, and often controversial moving force in modern music, has been the subject of a vast amount of literary criticism, philosophical discussions, and groundbreaking performances. Originally in French, Scelsi’s writings have been included in anthologies of prose, poetry, and memories published in French, Italian, and German. For the first time, this volume brings selected writings into English. His writings enlighten the creative process and facilitate further the understanding of his musical message. Following Eric Drott’s Preface, Franco Sciannameo and Alessandra Carlotta Pellegrini provide two introductory essays to Scelsi’s Meaning of Music, The Evolution of Harmony, The Evolution of Rhythm, Art and Satanism, Unity and Equality of the Arts, Sound and Music, and Art and Knowledge–writings spanning from the early 1940s to February 1987. Additionally, the editors place Scelsi’s aesthetical writings within a densely contextualized historical, social, and cultural landscape to provide scholarly yet approachable critical information. Iconographic plates, bibliography, discography and a comprehensive index complete the volume.